Inequality in healthcare use among older people in Colombia - Garcia-Ramirez, Jorge; Nikoloski, Zlatko; Mossialos, Elias (International journal for equity in health, 2020)
Background Since the early 1990s, Colombia has made great strides in extending healthcare coverage to its population. In order to measure the impact of these efforts, it is important to assess whether the introduction of universal health coverage has translated into equitable access to healthcare in the country, particularly for the elderly. Thus, in this study we assessed the inequality in utilization of health services among elderly patients in Colombia. In addition, we identified the determinants of healthcare utilization. Methods We analyzed the 2015 Colombian health, well-being and aging study (SABE). To classify determinants of healthcare use into predisposing, enabling and need factors, we employed the Anderson framework of healthcare utilization. Use of outpatient, inpatient and preventive health services constituted the dependent variables. We performed multivariate logistic regressions, estimated concentration indexes (CI) and performed decomposition analyses of the CIs to determine the contribution of various determinants to inequality of healthcare utilization. Results The study sample included 23,694 adults over 60-years-old. Wealth quintile, urban dwelling, health insurance type and multimorbidity predicted the utilization of all types of healthcare services except for hospitalization. Aside from inpatient care, pro-rich inequality in utilization of healthcare services was present. Wealth quintile and type of health insurance were the largest contributors to pro-rich inequality in use of preventive services. Conclusions While there has been progress in health insurance coverage for the elderly in Colombia, there are still equality challenges in the delivery of healthcare, especially for preventive and outpatient care. These inequalities are driven by individual characteristics such as wealth, urban residence, type of health insurance carried, and presence of multimorbidity. To address this issue, the Colombian health system should extend health insurance coverage to uninsured populations, as well as reduce barriers of access to healthcare services among poorest and the rural population receiving subsidized insurance.